mTORC1-Rps15 Axis Contributes to the Mechanisms Underlying Global Translation Reduction During Senescence of Mouse Embryonic Fibroblasts - Wu, Su; Xu, Siyao; Li, Ruofei; Li, Kecheng; Zhong, Xiaoqin; Li, Yingying; Zhou, Zhifen; Liu, Yi; Feng, Ran; Zheng, Jianfei; Songyang, Zhou; Liu, Feng (Frontiers in Cell and Developmental Biology, 2019)
The reduction of protein synthesis is a common feature in senescent cells and aging organisms, yet the underlying mechanisms are not fully understood. Here we show that both global mRNA translation and mTORC1 kinase activity are declined in a senescent model of mouse embryonic fibroblasts (MEFs). Furthermore, RNA-seq analyses from polysomal versus total mRNA fractions identify TOP-like mRNA of Rps15 whose translation is regulated by mTORC1 during MEF senescence. Overexpression of Rps15 delays MEF senescence, possibly through regulating ribosome maturation. Together, these findings indicate that the activation of mTORC1-Rps15 axis ameliorate senescence by regulating ribosome biogenesis, which may provide further insights into aging research.